Physicians' professional identities: a roadmap to understanding "value" in cardiovascular imaging. Issue 1 (December 2016) - Keller, Eric; Vogelzang, Robert; Freed, Benjamin; Carr, James; Collins, Jeremy
Abstract Background Quality improvement efforts in cardiovascular imaging have been challenged by limited adoption of initiatives and policies. In order to better understand this limitation and inform future efforts, the range clinical values related to cardiovascular imaging at a large academic hospital was characterized. Materials and methods 15 Northwestern Medicine physicians from internal medicine, cardiology, emergency medicine, cardiac/vascular surgery, and radiology were interviewed about their use of cardiovascular imaging and imaging guidelines. Interview transcripts were systemically analyzed according to constructivist grounded theory and combined with 56 previous interviews with interventional radiologists, interventional cardiologists, gynecologists, and vascular surgeons to develop a model describing specialty-specific values. This model was applied to the 15 pilot interviews focused on cardiovascular imaging, highlighting specialty specific differences in values and practice patterns. Transcripts were also reviewed independently by a cardiologist and 2 radiologists followed by a group discussion to assess reproducibility and achieve a consensus regarding the results. Results Differences in perceived value of cardiovascular imaging and use of guidelines among physicians were well explained by three value-associated identity categories (managers, diagnosticians, and fixers) that were further differentiated along three axes (broad v. focused-thinkers, complex v. definitive-answer-seekers, and public visibility). Conclusions Quality improvement in cardiovascular imaging may be limited by a lack of understanding and incorporation of the complexity of medical culture into ongoing initiatives. Both individually and during policy development, it is important to first understand the complexity of stakeholders' diverse perceptions of "value, " "quality, " and "appropriateness."